Effect of matrix elasticity on affinity binding and release of bioparticles. Elution of bound cells by temperature-induced shrinkage of the smart macroporous hydrogel - Galaev, Igor Yu (Langmuir : the ACS journal of surfaces and colloids, 2007)
The first step of bacterial or viral invasion is affinity and presumably multisite binding of bioparticles to an elastic matrix like a living tissue. We have demonstrated that model bioparticles such as inclusion bodies (spheres of about 1 microm in size) Escherichia coli cells (rods 1 x 3 microm), yeast cells (8 microm spheres), and synthetic microgel particles (0.4 microm spheres) are binding via different affinity interactions (IgG antibody-protein A, sugar-lectin, and metal ion-chelate) to a macroporous hydrogel (MH) matrix bearing appropriate ligands. The elastic deformation of the MH results in the detachment of affinity bound bioparticles. The particle detachment on elastic deformation is believed to be due to multipoint attachment of the particles to affinity matrix and the disturbance of the distance between affinity ligands when the matrix is deformed. No release of affinity bound protein occurred on elastic deformation. The efficiency of the particle release by the elastic deformation depends on the density of the ligands at the particle surface as well as on the elasticity of the matrix for relatively large particles. The release of the particles occurred irrespectively of whether the deformation was caused by external forces (mechanical deformation) or internal forces (the shrinkage of thermosensitive macroporous poly-N-isopropylacrylamide hydrogel on increase in temperature)